Aesthetic Needs of In-Service and Pre-Service Secondary Music Teachers in Korea - Yoon Jeong Jung (Universitas Negeri Semarang, 2026)
Aesthetic experience plays a pivotal role in fostering innovative thinking and emotional growth. In educational contexts, teachers’ engagement with aesthetic experiences contributes to instructional environments and enhances both their emotional well-being and the quality of music education. Aesthetic needs, which motivate individuals to seek and sustain aesthetic experiences, therefore warrant systematic investigation. This study examined the aesthetic needs of 88 in-service and pre-service secondary music teachers in South Korea, including 48 in-service and 40 pre-service teachers. The results indicated that female participants reported significantly higher levels of artistic needs and aesthetic needs in everyday life than males. In-service teachers also demonstrated significantly higher artistic needs than pre-service teachers. Participants with higher educational attainment reported significantly greater aesthetic needs related to built and natural environments. Artistic needs varied by age, with the highest levels observed among participants in their 40s. In addition, everyday aesthetic needs varied by teaching experience in a non-linear pattern, declining among teachers with 15–19 years of experience before recovering in the most experienced group. No statistically significant differences were found by undergraduate major, although participants majoring in composition reported slightly higher artistic needs than those in other majors. These findings indicate that the aesthetic needs of secondary music teachers are domain-specific, with each demographic factor associated with distinct subdomains rather than with aesthetic needs as a whole, supporting a multidimensional conceptualization of aesthetic needs. As the fulfillment of aesthetic needs may promote continued aesthetic engagement and support instructional quality, institutional support for teachers’ aesthetic experiences is warranted. Furthermore, the results highlight the importance of intentionally integrating aesthetic education into teacher preparation and professional development programs.